Quantum Dot Based Nano-Biosensors for Detection of Circulating Cell Free miRNAs in Lung Carcinogenesis: From Biology to Clinical Translation - Singh, Radha D.; Shandilya, Ruchita; Bhargava, Arpit; Kumar, Rajat; Tiwari, Rajnarayan; Chaudhury, Koel; Srivastava, Rupesh K.; Goryacheva, Irina Y.; Mishra, Pradyumna K. (Frontiers in Genetics, 2018)
Lung cancer is one of the most frequently occurring malignancies and the leading cause of cancer-related deaths in Southeast Asia. Over-diagnosis, excessive cost, risks associated with radiation exposure, false positive results and delay in the commencement of the treatment procedure questions the utility of low dose computed tomography as a reliable method for population-based screening. Therefore, identification of minimal-invasive biomarkers, able to detect malignancies at an early stage might be useful to reduce the disease burden. Circulating nucleic acids is emerging as an important source of information for several chronic pathologies including lung cancer. Out of these, circulating cell free miRNAs are reported to be closely associated with the clinical outcome of lung cancer patients and offers the potential of getting utilized as lung cancer biomarkers. Smaller size, sequence homology between species within the family, low concentration, and stability are some of the major issues involved and characterization and specific detection of miRNAs. To circumvent these problems, synthesis of a quantum dot based nano-biosensor might assist in sensitive, specific and cost-effective detection of differentially regulated miRNAs. The wide excitation and narrow emission spectra of these nanoparticles result in excellent fluorescent quantum yields with a broader color spectrum which make them ideal candidates for fluorescence resonance energy transfer-based multiplexing to facilitate the simultaneous study of multiple probes. In addition, photo-resistance and higher stability of these nanoparticles allows extensive exposure and offer state-of-the art sensitivity for miRNA targeting. A major obstacle for integrating QDs into clinical application is the QD induced cytotoxicity. QDs are composed of potentially toxic metal atoms and may elicit unexpected cytotoxicity due to the colloidal effects and photon-induced free-radical formation. However, the use of nontoxic shells along with surface modification not only overcome their toxicity issues, but also increases the ability of these nanoshells to quickly identify cancer-associated molecular markers in a non-invasive mode. The present review not only illustrates the importance of ccf-miRNAs in lung cancer diagnosis but also discusses the translational prospect of developing quantum dot based nano-biosensor for rapid diagnosis of disease specific ccf-miRNAs in lung cancer.